OPTIMIZATION OF PRODUCTS REGISTRATION ON PRODUCTION AT APPLICATION OF MODERN TECHNOLOGIES - A. U. Gapanuk (Литьë и металлургия)
It is shown that calculation of production at RUP «BMZ» with application of modern technologies will enable to give more attention to its production and sale.